2017
DOI: 10.1097/md.0000000000009342
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin-1-related peptides as the prognostic biomarkers for heart failure

Abstract: Background:Most studies reported that high plasma endothelin-1 (ET-1), big ET-1, and C-terminal proET-1 (CT-proET-1) were correlated with poor prognosis of heart failure (HF). However, available evidence remains controversial. To help solve the debate, we collected all the available studies and performed a meta-analysis.Methods:We searched the databases covering Embase, PubMed, Ovid, and Web of Science on June 28, 2017. The hazard ratio (HR) or risk ratio (RR) and its 95% confidence intervals (CIs) were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…A recent metaanalysis focused on ET-1, pro-endotelin-1, and CT-pro-ET-1 demonstrated that increased levels of all three isoforms of the endothelin family were associated with poor prognosis or mortality in HF populations. 35 In the light of increased ET-1 levels and their association with elevated pulmonary vascular resistance, which in turn leads to right ventricular dilatation and failure, our association between CT-pro-ET-1 levels and right ventricular diameter are sound and logical. As ET-1 is highly expressed in the lung, it can contribute to a strong vasoconstriction of the pulmonary arteries and veins and, consequently, to pulmonary hypertension.…”
Section: C-terminal Pro-endothelin-1mentioning
confidence: 88%
“…A recent metaanalysis focused on ET-1, pro-endotelin-1, and CT-pro-ET-1 demonstrated that increased levels of all three isoforms of the endothelin family were associated with poor prognosis or mortality in HF populations. 35 In the light of increased ET-1 levels and their association with elevated pulmonary vascular resistance, which in turn leads to right ventricular dilatation and failure, our association between CT-pro-ET-1 levels and right ventricular diameter are sound and logical. As ET-1 is highly expressed in the lung, it can contribute to a strong vasoconstriction of the pulmonary arteries and veins and, consequently, to pulmonary hypertension.…”
Section: C-terminal Pro-endothelin-1mentioning
confidence: 88%
“…When 32 studies with 18497 HF patients were summarized in the meta-analysis, it was shown that plasma ET-1 and its related peptides were associated with poor prognosis and mortality in diverse spectrum of HF populations[ 272 ]. On the other hand, a meta-analysis of randomized clinical trials showed that neurohumoral antagonism of ET receptors in HF patients improved cardiac output, pulmonary and systemic hemodynamics but had a modest effect on clinical outcomes[ 273 ].…”
Section: Laboratory Biomarkers Of Sympathetic Nervous System Activatimentioning
confidence: 99%
“…Therefore, more extensive characterization of signalling molecules in patients might be important predictors of drug efficacy. Importantly, we expect that Brd4 inhibition will be less effective in severe and/or late stages of heart failure as PKA activity is reduced (41) and levels of endothelin-1 or its precursors (6668) increases. Chronic infusion of these neurohormones with mice is required to determine how the receptor-specific effects of Brd4 inhibition effects cardiac remodelling.…”
Section: Discussionmentioning
confidence: 99%